Breastfeeding practices and factors associated with it: A cross sectional study among tribal women in khardi primary health centre, Thane, India - Prateek Sudhakar Bobhate; Saurabh Rambiharilal Shrivastava (Universiti Kebangsaan Malaysia, 2012)
India is home to large number of under-five deaths and underweight children in the world which is mainly because of improper breastfeeding practices. Hence the study was conducted to assess the breastfeeding practices in tribal settings so that proper interventions can be planned by the health system staff to reduce infant morbidity and mortality. Methods Cross-sectional study of three months duration from June 2011 to August 2011was conducted in tribal area of Khardi in Thane district amongst women who had delivered within one year of the study. This study was conducted in Khardi Primary Health Centre (PHC) which comprises of eight sub-centres. Five sub-centres among these eight sub-centres were selected randomly using lottery method. All tribal women, with infants between six months to twelve months of age, registered with these five sub-centres during their antenatal period were included as subjects. 153 such women were identified using universal sampling with the help of Auxillary Nurse Midwives (ANM) and Anganwadi Workers (AWW). 21 women were excluded due to non availability. House to house visits were paid to these subjects & they were then interviewed face to face using a questionnaire after taking their informed consent. Dependent variable was breastfeeding practices including exclusive breastfeeding and independent variables were all the socio-demographic factors influencing breastfeeding. Analysis was done with SPSS version 16. Results More than half (67.4%) infants were exclusively breast fed (EBF) up to six months of age. Pre-lacteal feeds were given to 23.5% infants while colostrum was not given to 15.2% infants. Practice of EBF was found to be significantly associated with advice regarding EBF during antenatal period, education status, parity of mother and sex of child. Conclusions 67.4% of the infants were exclusively breastfed till six months of age. Religion, education of the mother, number of children of study subjects, sex of the baby and knowledge about EBF was found to be significantly associated with exclusive breastfeeding.